Motivation and Needs of Bangkok Fire and Rescue Department Officials on Further Education in Disaster Management Program - Sripramai, Keerati; Phimsaart, Kanthasit; Thongtao, Kanchai; Ruenwicha, Natee (วารสารศึกษาศาสตร์ มหาวิทยาลัยสงขลานครินทร์ วิทยาเขตปัตตานี, 2023)
The research aimed at studying and comparing the motivation and needs of Bangkok Fire and Rescue Department officials on further studying in disaster management program. The samples of this research are 327 officials working in 2021. Content validity was examined by experts. The confidence in the knowledge questionnaire, the KR-20 formula is 0.76, and the Cronbach's alpha coefficient is 0.77. The research instrument was a questionnaire consisting of two parts and the results of the study revealed the following. The results of the motivation and needs for studying in the field of disaster management program were found the overall at high levels ( = 4.06). They were in all four aspects including personal motivation and needs ( =4.19), social motivation and needs ( = 4.16), occupational motivation and needs ( = 3.99), academic motivation and needs ( = 3.90) at high level, respectively. The result of the motivation and needs for comparison in the field of disaster management program, classified by gender; status; domicile; the highest level of education; GPA; average monthly income; and sources of funds used for pursuing a bachelor's degree, was non-statistically different at the .05 level. For further results, those classified by age; distance from residence to Navamindradhiraj University; service life; and job position level, were statistically different at the .05 level. The results show that officers are more likely to participate in disaster management program when they perceive that Bangkok Fire and Rescue Department supports the time and resources to succeed in career paths.